Surgical performance when inserting non-locking screws: a systematic review. Issue 1 (3rd January 2020) - Fletcher, James W.A.; Wenzel, Lisa; Neumann, Verena; Richards, R. Geoff; Gueorguiev, Boyko; Gill, Harinderjit S.; Preatoni, Ezio; Whitehouse, Michael R.
Abstract : Billions of screws are inserted by surgeons each year, making them the most commonly inserted implant. When using non-locking screws, insertion technique is decided by the surgeon, including how much to tighten each screw. The aims of this study were to assess, through a systematic review, the screw tightness and rate of material stripping produced by surgeons and the effect of different variables related to screw insertion. Twelve studies were included, with 260 surgeons inserting a total of 2793 screws; an average of 11 screws each, although only 1510 screws have been inserted by 145 surgeons where tightness was measured – average tightness was 78±10% for cortical ( n = 1079) and 80±6% for cancellous screw insertions ( n = 431). An average of 26% of all inserted screws irreparably damaged and stripped screw holes, reducing the construct pullout strength. Furthermore, awareness of bone stripping is very poor, meaning that screws must be considerably overtightened before a surgeon will typically detect it. Variation between individual surgeons' ability to optimally insert screws was seen, with some surgeons stripping more than 90% of samples and others hardly any. Contradictory findings were seen for the relationship between the tightness achieved and bone density. The optimum tightness for screws remains unknown, thus subjectively chosen screw tightness, which varies greatly, remains without an established target to generate the best possible construct for any given situation. Work is needed to establish these targets, and to develop methods to accurately and repeatably achieve them. Cite this article: EFORT Open Rev 2020;5:26-36. DOI: 10.1302/2058-5241.5.180066